Effect of main family caregiver’s anxiety and depression on mortality of patients with moderate-severe stroke - Jianting Zhao (Nature Portfolio, 2021)
Abstract Anxiety and depression are common mental illness in stroke caregivers, resulting in significant stress to the emotion health of caregivers. Caregivers’ emotion can seriously affect the recovery rate of stroke patient, therefore, how to control and affect the caregivers’ anxiety and depression is of great importance. Here three multiple centers observation and validation study were performed to screen out the risk factors for development of anxiety and depression in main family caregiver, and the effect of anxiety and depression of family caregivers on 6-month mortality of patients with moderate-severe stroke. The severity of the stroke, the duration of care time and the medical payment associated with increased risk of anxiety and depression. Anxiety and depression of main family caregivers are associated with increased risk 6-month mortality of patients with moderate-severe stroke. Therefore, the support provided to the family caregivers might have positive effect on prognosis of the patients with stroke.